Jet mixing of water in crude oil pipelines - Fernando, L. M. (Cranfield University, 1990)
The jet mixing of water in crude oil pipelines by single nozzle and multi-nozzle mixers was studied by dividing the mixing domain into to three regions. the penetration. near field and farfield regions. At the penetration region the quantitative experimental data were aided by a flow visualisation study in an attempt to to form fundamental semi-empirical correlations to estimate the entrainment rate of stratified water from the bottom and the Sauter mean diameter of the entrained water droplets for a single nozzle jet mixer. The flow field diagnostics into the near field region. defined as the region where high level of swirl and mixing is occuring. were conducted theoretically using computational fluid dynamic code "Phoenics" and experimentally through LOA measurements and flow visualisation. The entrainment rate found in penetration region was treated as a source term for theoretical analysis. Experimental analysis of this region was conducted in single phase flow for two mixer nozzles i) Single nozzle mixer and ii). Existing multi-nozzle mixer. Experimental results have revealed that the swirl velocities decay faster for higher velocity ratios and their dependence on Reynolds number (in the range 27600 to 48400) is weak. Higher velocity ratios would generate and dissipate higher levels of energy, therefore break up water droplets to smaller sizes and increase the eddy viscosity. The dispersion strength due to swirl decays faster and the gravity settling begins earlier. As the flow reaches downstream. approximately four diameters. the distribution of velocities (mean and RMS) flattens out and their magnitude begins to close up for the two mixers. when their momentum ratios are equal. It was also shown that the swirl velocities (at axis) die away. approximately at the same axial point for both of the nozzles. The multi-nozzle mixer is shown to be better in two characteristics; i). The mixing is faster and ii) The jet energy is more evenly distributed in the vicinity of the injection cross section. hence improving the quality of the droplet size distribution. Besides providing information to aid understanding of the complex flow in the mixer zone. the experimental data is believed to be of sufficient quality and quantity to improve the present simple modelling procedures as well as to be used as test cases for assessment of the predictive accuracy of more elaborate computational models. Comparision with computational results (of low velocity ratios) shows the agreement with swirl velocities is reasonable. but not always acceptable for mean axial velocities. However. the computational model predicts the near field jet trajectory reasonably well. The flow visualisation of dispersion of passive contaminant agrees qualitatively with the contours of the passive contaminant. In the far field region. where the swirl has decayed. the flow behaves two dimensionally. Therefore. an exact solution was obtained for two dimensional water conservation equation. The boundary conditions were specified by using sticking probability constants. A relationship was obtained to specify eddy viscosity through turbulent kinetic energy. The turbulent kinetic energy and swirl decay were estimated from LDA experimental data. This solution can be used to study the developing characteristics of water concentration profiles along the far field region of the pipeline.